1981
DOI: 10.3382/ps.0601152
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Diet Composition on Vanadium Toxicity in Laying Hens

Abstract: Vanadium added to laying rations as NH4 VO3, VOCl2 or VOSO4 at levels of 20 to 80 ppm resulted in a rapid and substantial reduction in albumen quality as measured by Haugh units. Dietary vanadium also resulted in reduced egg production, egg weight, body weight, feed consumption, and poorer shell quality as measured by specific gravity. Ascorbic acid at .4 to .5% effectively protected the hen from the reduction in albumen quality, egg production, and body weight for up to 40 ppm vanadium, but not the reduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…However, other investigators did not demonstrate any significant changes in the diet and fluid intake (Bishayee and Chatterjee 1995;De Tata et al 2000;Poggioli et al 2001) or in body weight gain (Dai et al 1995;Thompson et al 2002) after treating rats with vanadate or vanadyl in drinking water. A reduction in diet intake and/or body weight gain after administration of vanadium was also shown in other animals: in laying hens (Ousterhout and Berg 1981), sheep (Hansard et al 1982), chicks (Cupo and Donaldson 1987), and in male mice (Llobet et al 1993). Reduced fluid intake after SMV treatment, as it was shown (Table 3), might be caused by an altered taste of vanadate solution which might lead to development of rats' aversion to drink, and in consequence, cause its decreased consumption.…”
Section: Discussionmentioning
confidence: 62%
“…However, other investigators did not demonstrate any significant changes in the diet and fluid intake (Bishayee and Chatterjee 1995;De Tata et al 2000;Poggioli et al 2001) or in body weight gain (Dai et al 1995;Thompson et al 2002) after treating rats with vanadate or vanadyl in drinking water. A reduction in diet intake and/or body weight gain after administration of vanadium was also shown in other animals: in laying hens (Ousterhout and Berg 1981), sheep (Hansard et al 1982), chicks (Cupo and Donaldson 1987), and in male mice (Llobet et al 1993). Reduced fluid intake after SMV treatment, as it was shown (Table 3), might be caused by an altered taste of vanadate solution which might lead to development of rats' aversion to drink, and in consequence, cause its decreased consumption.…”
Section: Discussionmentioning
confidence: 62%
“…Moreover, the embryotoxic, fetotoxic, and teratogenic potential of vanadium sulfate pentahydrate have been evaluated in Swiss mice [10]. In vivo studies with chickens, the results have shown that dietary vanadium reduced egg production, egg weight, body weight, feed consumption, and poorer shell quality as measured by specific gravity [11]. Certainly, vanadium toxicity is decreased with increasing dietary protein [12].…”
Section: Introductionmentioning
confidence: 98%
“…For laying hens, adding Cr to the basal diet significantly alleviated the detrimental effects of V on interior egg quality in one laboratory (Jensen and Maurice, 1980), but not in another (Ousterhout and Berg, 1981). Recently, Cr also failed to counteract the deleterious effect of V on albumen quality in a study in the authors' laboratory (Benabdeljelil and Jensen, 1989).…”
Section: Introductionmentioning
confidence: 89%
“…The adverse effects of dietary V on albumen quality have been reported by Berg et al (1963), Jensen et al (1978), Ousterhout and Berg (1981), and Eyal and Moran (1984). Berg et al (1963) found that 30 ppm of V fed as ammonium metavanadate to laying hens depressed egg production, while only 15 to 20 ppm of V were required to lower albumen quality.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation